KESIAPSIAGAAN KOMUNITAS SEKOLAH DASAR TERHADAP BENCANA ROB DI KECAMATAN SAYUNG, KABUPATEN DEMAK TAHUN 2014 (SEBAGAI BAHAN PENGAYAAN PEMBELAJARAN GEOGRAFI PADA MATERI POKOK MITIGASI DAN ADAPTASI BENCANA ALAM KELAS X) - Reva, Shinta Ayu (Pendidikan Geografi, 2014)
ABSTRACTThe objectives of this research are to investigate: (1) the preparedness of Primary School teachers in Sayung sub-district to deal with inundation disaster; (2) the preparedness of Primary School students in Sayung sub-district to deal with inundation disaster; (3) the preparedness of Primary School institutions in Sayung sub-district to deal with inundation disaster; and (4) the preparedness of communities of Primary Schools in relation to spatial analysis of schools in coastal area in Sayung sub-district. This research used the descriptive qualitative research method. Its population was communities of 8 State Primary Schools exposed to inundation in Sayung sub-district. The samples of research were State Primary Schools in Bedono, Sriwulan, Timbulsloko, and Surodadi villages exposed to inundation, teachers, school institutions, and students. They were taken by using the snowball sampling technique. The data of research were collected through in-depth interview, observation, and documentation. The validity of data used triangulate. They were analyzed by using the cognitive test and attitude scale of teachers, students, and school institutions to deal with the inundation disaster. The results of cognitive test and attitude scale were to classify the preparedness of teachers, students, school institutions, and communities of Primary Schools to deal with inundation disaster. The results of research are as follows: 1) One Primary School has teachers with the high-category preparedness to deal with inundation disaster, and seven schools have teachers with medium-category preparedness to deal with inundation disaster. 2) Three primary schools have students with the high-category preparedness to deal with inundation disaster, and five schools have the medium-category preparedness to deal with inundation disaster. 3) Two school institutions have the high-category preparedness to deal with inundation disaster, and six school institutions have the medium-category preparedness to deal with inundation disaster. 4) Four communities of Primary Schools have the high-category preparedness to deal with inundation disaster, and other four communities of Primary Schools have the medium-category preparedness to deal with inundation disaster. The differentiator of preparedness of one school from other schools is human resources. Keywords: Inundation, preparedness, and school